PEMBERDAYAAN POSYANDU DENGAN MEMBERIKAN EDUKASI GIZI SEIMBANG SEBAGAI UPAYA PENCEGAHAN DAN PENANGANAN STUNTING PADA BALITA - Rizky Tampubolon, nurhannifah; Andreana, Delvie; Amirah Rizka, Syafah; Rahayu, Venessa; Nadila, Nadila; Arfa Dewi, Suci; Siti Aisyah, Bunaiya; Novita, Rani; Ramadhan, Gilang; Bintang Jilena Sianturi, Sry; Windy, Septya (Jurnal LENTERA, 2024)
SStunting is still a child health problem in Indonesia with a fairly high prevalence, namely 21.6%. The government has made various efforts to tackle the problem of stunting, especially in Benteng Hulu Village, Siak Regency, which is one of the focus locations for handling stunting. The aim of this activity is to increase parents' knowledge about balanced nutrition for toddlers as a form of effort to prevent and treat stunting. The activity method is carried out in collaboration with posyandu cadres for stunting education using audiovisual media: videos, flip sheets and leaflets with material on nutrition and stunting problems, efforts to prevent and handle stunting, and developing balanced nutritional intake for toddlers. The educational activity involved 37 respondents, namely mothers with toddlers. The results obtained were that the average respondent before being given stunting education had a poor level of understanding (51.4%), and a sufficient level of understanding of 48.6%. After being provided with education, there was an increase in understanding to sufficient (40.5%) and a good level of understanding (59.5%). In addition, there was an increase in skills in conducting health education among posyandu cadres. It is hoped that this educational activity can be continued routinely at the posyandu by cadres with a combination of educational media so that the knowledge provided can change people's lifestyle behavior to become healthier